2011
DOI: 10.1094/fg-2011-0819-03-rs
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Sorghum Forages for Limited and Full Irrigation and Rainfed Conditions in Semiarid, Subtropical Environments

Abstract: Sorghum (Sorghum bicolor L.) forage producers in semiarid regions must maximize yield with reduced irrigation. Dry matter yields of furrow‐irrigated sorghum forage [conventional and photoperiod‐sensitive sorghum‐sudangrass (Sorghum bicolor var Sudanese) hybrids (SS and PS, respectively) and forage sorghum (FS)] managed for hay in cultivar evaluations (randomized complete blocks with four replications) were compared from two years each of full irrigation (FULL: 4 furrow irrigations/year, applying approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…1). Lauriault et al (9) suggested that late season moisture deficits likely have a greater negative impact on sorghum forage yield than any positive impact of adequate moisture earlier in the season in one‐ and two‐cut systems. In the present study, however, there appeared to also be a positive impact when seedling zone moisture was adequate at planting time (1).…”
Section: Planting Date and Sorghum Type Effects On Forage Yieldsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Lauriault et al (9) suggested that late season moisture deficits likely have a greater negative impact on sorghum forage yield than any positive impact of adequate moisture earlier in the season in one‐ and two‐cut systems. In the present study, however, there appeared to also be a positive impact when seedling zone moisture was adequate at planting time (1).…”
Section: Planting Date and Sorghum Type Effects On Forage Yieldsmentioning
confidence: 99%
“…Because of the decline in available water for irrigation in these regions, producers must adapt their cropping practices (1), and sorghum forage producers often must resort to single‐cut systems without irrigation as their only feasible option (9,10). Lauriault et al (9), in the Southern High Plains of eastern New Mexico, compared performance of FS, SS, and PS hybrids in years of plentiful irrigation, limited irrigation, and no irrigation. They (9) concluded that in a single‐cut system without irrigation, SS yields were significantly reduced compared to PS and tended to be lower than FS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in teff as hay for horses also has grown in the southwestern USA where the predominant warm‐season annual forages are sorghums [ Sorghum bicolor (L.) Moench and S. bicolor var. Sudanese ] (5,12,13), which are not suitable for horses (13) and can pose problems for cattle (3,13).…”
Section: Introductionmentioning
confidence: 99%